Exploring the Impact of Data Quality on Decision-Making Processes in Information Intensive Organizations - Khong, Isaac; Aprila Yusuf, Natasya; Nuriman, Arbi; Bayu Yadila, Ahmad (APTISI Transactions on Management (ATM), 2023)
This study investigates the influence of data quality on decision-making processes within organizations that heavily rely on information for their operations. With the increasing digitalization and proliferation of data in today's business landscape, the quality of data has emerged as a critical factor in ensuring accurate and effective decision-making. Through a comprehensive review of existing literature and an empirical analysis, this research aims to shed light on the relationship between data quality and decision-making outcomes. The study employs a mixed-methods approach, utilizing both qualitative interviews and quantitative surveys to gather insights from professionals across various information-intensive sectors. The findings reveal that data quality significantly impacts the accuracy, reliability, and timeliness of decisions made within these organizations. Moreover, the study identifies key challenges that organizations face in maintaining data quality and suggests potential strategies to enhance decision-making processes. The results of this research contribute to a deeper understanding of the pivotal role data quality plays in the success of information-intensive organizations and provide practical implications for managers and decision-makers.